Application of Simultaneous Inversion Method To Predict The Lithology And Fluid Distribution in “X” Field, Malay Basin. - Binti Abdullah, Ashley Aisyah Yoong (Universiti Teknologi PETRONAS, 2016)
Reservoir characterization is one of the most crucial processes in the exploration of hydrocarbons. Thus, having sufficient information such as the lithology and fluid distribution of a reservoir is vital. With the application of Simultaneous Seismic Inversion, we will be able to improve the prediction of the lithology and fluid distribution of the prospect area, as it generates information such as Density (ρ), Lambda-rho (λρ) (Incompressibility), and Mu-rho (μρ) (Rigidity). Real data from the Malay basin were used to show the effectiveness of this method in enhancing the resolution and characterizing the gas sand layer of the prospect.